1997
DOI: 10.2981/wlb.1997.028
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in sage grouse Centrocercus urophasianus populations in western North America

Abstract: Available data indicate that sage grouse Centrocercus urophasianus have declined throughout their range. This species presently occurs in 11 U.S. States and in two Canadian provinces. In nine states having long-term data, breeding populations have declined by 17-47% (x = 33%) from the long term average. Six states have long-term information on sage grouse produc tion. In five of these states, production has declined by 10-51% (x = 25%) from the long-term average. Habitat deterioration, loss, and fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
160
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(164 citation statements)
references
References 15 publications
3
160
0
Order By: Relevance
“…All previously published analyses of sage-grouse populations have documented decreases throughout the species' range (Connelly and Braun 1997, WAFWA 2008, Garton et al 2011. Our results support these findings and provide compelling evidence that most populations have continued to decline over the last 6 years reaching a low in 2013 below 50,000 males attending leks range-wide, an 8 fold decline from the late 1960s.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…All previously published analyses of sage-grouse populations have documented decreases throughout the species' range (Connelly and Braun 1997, WAFWA 2008, Garton et al 2011. Our results support these findings and provide compelling evidence that most populations have continued to decline over the last 6 years reaching a low in 2013 below 50,000 males attending leks range-wide, an 8 fold decline from the late 1960s.…”
Section: Discussionsupporting
confidence: 81%
“…Connelly and Braun (1997) concluded that by 1994 breeding populations had declined by 17-47% from long-term averages. Connelly et al (2004) reported that sagegrouse populations declined at an overall rate 2.0% per year from .…”
Section: Introductionmentioning
confidence: 99%
“…Despite management and research efforts that date to the 1930s (Girard, 1937), breeding populations of sage-grouse (Centrocercus urophasianus), a once abundant sagebrush-steppe obligate, have declined by at least 17-47% throughout much of their range (Connelly and Braun, 1997). Current distribution extends south from southern Saskatchewan and Alberta (Canada), western North and South Dakota, Montana, Wyoming, Utah, Colorado, eastern Washington, Idaho, Oregon, Nevada, and northeastern California (USA) (Johnsgard, 1983;Drut, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…landscapes has emerged as a topical conservation issue [1]. Rangewide loss, fragmentation, and degradation of sagebrush communities in the early part of the last century have been attributed to agricultural conversion [2,3], urbanization [4], excessive herbivory [5], altered fire regimes [6], and invasion of exotic plants [3]. As a result, the long-term sustainability of many wildlife populations dependent on sagebrush has been compromised [4,7].…”
Section: Introductionmentioning
confidence: 99%